PORTRAIT OF CONTEXTUAL TAFSIR IN INDONESIA: A STUDY OF SYSTEMATIC LITERATURE REVIEW - Akbar, Faris Maulana (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2021)
Contextual interpretation is a popular discourse in the contemporary era in the study of global interpretation. In Indonesia, this discourse is also rolling and has become a hot topic of discussion among commentators. Contextual interpretation then becomes the new alternative chosen by commentators in studying the Qur’an. To prove this hypothesis and at the same time find out to what extent the contextual interpretation discourse has been discussed, the authors examine journal articles from MORAEF, Garuda, and Google Scholar using a systematic literature review method. The journal article search used the keywords “tafsir”, “interpretation”, “contextual”, and “al-Qur’an”, which were applied to the three search sources in the period 2009-2020. This study found that the discourse of contextual interpretation received a positive response in Indonesia. However, there are no significant developments or updates. Quantitatively, the address is proliferating from year to year from 2009-to 2020. Meanwhile, the quality of the study is stagnant and undeveloped. This is because the discourse of contextual interpretation in Indonesia is identical to the figure of Abdullah Saeed. Saeed’s methodology has become a reference for many researchers because it is considered to have wooden steps compared to other contextualist thinkers.